2020
DOI: 10.1155/2020/7524726
|View full text |Cite
|
Sign up to set email alerts
|

Toxic Epidermal Necrolysis (TEN)/Stevens-Johnson Syndrome (SJS) Epidemiology and Mortality Rate at King Fahad Specialist Hospital (KFSH) in Qassim Region of Saudi Arabia: A Retrospective Study

Abstract: Background. Toxic epidermal necrolysis (TEN) and Stevens-Johnson syndrome (SJS) are life-threatening conditions caused by drug reactions. There are multiple causative drugs and different risk factors associated with SJS/TEN. Objectives. To study the epidemiology of SJS/TEN and associated mortality rate in Qassim region, Saudi Arabia. Methodology. A retrospective chart review of all patients with the diagnosis of SJS/TEN who were admitted to King Fahad Specialist Hospital (KFSH) in Qassim region, Saudi Arabia, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 12 publications
2
7
0
Order By: Relevance
“…For the remaining four cases, the causative agents were not identi ed (one of them was suspected to be allopurinol or empagli ozin). These ndings are consistent with those of two previous studies from Saudi implicating antibiotics (including trimethoprim/sulphamethoxazole (TMP/SMZ), amoxicillin/clavulanate, and cipro oxacin) as the most common cause of TEN/SJS [3,4]. A previous study from Japan on 52 cases of SJS and 65 cases of TEN reported medications to be the causative agents in all the TEN cases and most SJS cases [14].…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…For the remaining four cases, the causative agents were not identi ed (one of them was suspected to be allopurinol or empagli ozin). These ndings are consistent with those of two previous studies from Saudi implicating antibiotics (including trimethoprim/sulphamethoxazole (TMP/SMZ), amoxicillin/clavulanate, and cipro oxacin) as the most common cause of TEN/SJS [3,4]. A previous study from Japan on 52 cases of SJS and 65 cases of TEN reported medications to be the causative agents in all the TEN cases and most SJS cases [14].…”
Section: Resultssupporting
confidence: 91%
“…A recent retrospective survey at the King Fahad Specialist Hospital (KFSH) in the Qassim region between January 2014 and January 2019 identi ed 10 patients with TEN/SJS, and one of them died [3]. The culprit medications included amoxicillin/clavulanic acid in three cases, carbamazepine in two, and acetaminophen, azithromycin, cipro oxacin, and levetiracetam in one case each and an unknown cause in one case [3]. Another review of 13 patients diagnosed with TEN/SJS at the King Abdullah Medical City (KAMC), the Holy Makkah, between March 2003 and March 2010 revealed a mortality of 15% (two patients) [4].…”
Section: Introductionmentioning
confidence: 99%
“…The differences among the populations in terms of medication consumption habits and the scales of reaction from the medications they often use with the population’s pharmacogenetic tendency will affect the frequency of SJS/TEN occurrence. 21 …”
Section: Discussionmentioning
confidence: 99%
“…All 30 articles included in this systematic review were observational studies (seven cohort studies and 23 cross-sectional studies). Of the 30 studies, 26 (86.66%) obtained their data from an administrative database and/or patient interviewing [3,[14][15][16][17][18][21][22][23][24]26,[28][29][30][31][32][34][35][36][37][38][39][40][41], two studies (6.66%) from a survey [33,42], and two studies (6.66%) did not specify the data source [19,27]. Most of the studies reported the outcomes over a short period.…”
Section: Methodological Characteristics Of Included Studiesmentioning
confidence: 99%
“…All articles were written in English and conducted in Saudi Arabia. Thirteen studies were from the Riyadh region [3,[14][15][16][17][18][19][20][21][22][23][24][25], nine were from the Makkah region [26][27][28][29][30][31][32][33][34], three studies were from the Eastern region [35][36][37], three studies were from the Qassim region [38][39][40], one study was from the Najran region [41], and one study covered entire Saudi Arabia [42]. In relation to the range of years of publication, the oldest article was from 2012, and the latest was from 2021.…”
Section: General Characteristics Of Included Studiesmentioning
confidence: 99%